Good Corporate Governance and Leverage Control Variables at Agency Cost: Non Financial Companies in Indonesia - Prasastine, Sachqnava Aguesta; Yulianto, Arief (Universitas Negeri Semarang, 2022)
This study aims to determine the effect of good corporate governance and leverage as a control variable on agency costs. Agency cost is proxied by asset turnover ratio and good corporate governance is proxied by institutional ownership, managerial ownership and independen board of commissioners. The population in this study are non-financial companies listed on the Indonesia Stock Exchange in 2008-2020. The sample in the study was 60 companies obtained through purposive sampling technique. The study used multiple linear regression using the random effect model. This study has the result that institutional ownership and independen board of commissioners have an insignificant negative effect on agency costs. Managerial ownership has a significant negative effect on agency costs. Leverage as a control variable has a significant negative effect on agency costs.